2020
DOI: 10.7759/cureus.9418
|View full text |Cite
|
Sign up to set email alerts
|

Significant Impact of the Ketogenic Diet on Low-Density Lipoprotein Cholesterol Levels

Abstract: It is well known, based on the previous research, that a ketogenic diet leads to an improvement in the lipid profile and decreases cardiovascular risk factors such as hypertension. However, recent studies have also reported increased levels of total cholesterol and low-density lipoprotein cholesterol (LDL-C) as a result of this diet. It has been postulated that this elevation in LDL-C would not likely increase cardiovascular complications due to the large LDL-C particle size. In this case report, we present a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…This difference was no longer signi cant at 12 months. Recently research suggested that the association of LDL-C to cardiovascular risk varies based on particle size, and LCD and KD tend to increase LDL-C particle size [31,32], indicating that the increase in LDL-C alone may not be accompanied by an increased cardiovascular risk [25]. In addition, no participants experienced severe ketosis symptoms, a condition that can be harmful when ketone production is unregulated.…”
Section: Discussionmentioning
confidence: 99%
“…This difference was no longer signi cant at 12 months. Recently research suggested that the association of LDL-C to cardiovascular risk varies based on particle size, and LCD and KD tend to increase LDL-C particle size [31,32], indicating that the increase in LDL-C alone may not be accompanied by an increased cardiovascular risk [25]. In addition, no participants experienced severe ketosis symptoms, a condition that can be harmful when ketone production is unregulated.…”
Section: Discussionmentioning
confidence: 99%
“…57,63,64 This type of diet increases blood levels of triglycerides and cholesterol, both associated with an increased risk of cardiovascular diseases. 64 The low carbohydrate content of keto diets leads to a significant amount of dietary protein being used for the production of glucose via gluconeogenesis. This involves the deamination of amino acids with the subsequent production of urea.…”
Section: Nutrition/diet Subsystemmentioning
confidence: 99%
“…These diets, commonly known as keto diets, are low in carbohydrate, high in lipid and adequate protein. Many keto diets are animal-based with high lipid content (as much as 75%), in particular saturated fats as well as cholesterol. ,, This type of diet increases blood levels of triglycerides and cholesterol, both associated with an increased risk of cardiovascular diseases . The low carbohydrate content of keto diets leads to a significant amount of dietary protein being used for the production of glucose via gluconeogenesis.…”
Section: Detailed Description Of the Socmementioning
confidence: 99%
“…A ketogenic diet consists of a high-fat, low-carbohydrate consumption that is restricted to 5%-10% of the daily required intake of carbohydrates and swapping the vast majority of it with nutritional fat and sufficient protein (1 g/kg) [ 7 ]. A typical KD often includes foods such as coconut oil, butter, cheese, avocado, eggs, and meat [ 8 ]. These foods are all high in fat and protein while low in carbohydrates, which is a cornerstone of a ketogenic diet.…”
Section: Introductionmentioning
confidence: 99%